SOCIAL SUPPORT PADA KORBAN KEKERASAN DALAM RUMAH TANGGA - Afdal Afdal; Aminatul Ihsani; Siti Juwaiyriyah; Wiwin Andriani; Denia Syapitri (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
Nowadays, cases of domestic violence are increasing which have many impacts on victims of domestic violence, both physically and psychologically. This study uses a qualitative approach with a descriptive study that aims to describe social support for victims of domestic violence. The subjects of this study amounted to 2 people who were victims of domestic violence, namely wives who were 64 years old (EM) and 42 years old (YM). Data were collected through interviews, documentation, and observations which were then analyzed qualitatively. The results of this study indicate that the occurrence of domestic violence is caused by economic factors because the husband does not work and the family needs are not fulfilled. In this case, the need for the role of certain parties to minimize the occurrence of domestic violence, first, victims of domestic violence can share with relatives and friends who are considered suitable to really focus and deal with the problems at hand; second, the community knows and understands about gender equality, the risks of domestic violence and various problems identified by efforts to expand public awareness in tackling domestic violence; third, forming an organization that involves the community through local community leaders, religious leaders and cooperating with public authorities in expanding cooperation with the government in overcoming domestic violence; The four counselors carry out a counseling process, one of which is based on the theory of social support that is tailored to the client's needs based on the counselor's considerations.